Private Job Placement Services: A Microeconometric Evaluation for Germany - Henrik Winterhager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In recent years, coinciding with the discussion led in many OECD countries, Germany has started to contract out placement services for the unemployed to private agencies. Whereas in the Netherlands and Australia the whole system of employment services was reorganized at once, making an econometric evaluation difficult, only a small part of services has been contracted out so far in Germany. In this paper a microeconometric evaluation of this system using propensity score matching is presented. The effects on the employment probabilities of the unemployed are small and negative so far. A theoretical analysis suggests that this might be explained by deficits in the contract management.
Keywords: H25; J68; 330; Job Placement; Contracting Out; Active Labor Market Policy; Matching; Personalberatung; Arbeitsvermittlung; Reform; Wirtschaftspolitische Wirkungsanalyse; Beschäftigungseffekt; Schätzung; Deutschland